2011
DOI: 10.1007/s10801-011-0332-2
|View full text |Cite
|
Sign up to set email alerts
|

Galois groups of multivariate Tutte polynomials

Abstract: The multivariate Tutte polynomial $\hat Z_M$ of a matroid $M$ is a generalization of the standard two-variable version, obtained by assigning a separate variable $v_e$ to each element $e$ of the ground set $E$. It encodes the full structure of $M$. Let $\bv = \{v_e\}_{e\in E}$, let $K$ be an arbitrary field, and suppose $M$ is connected. We show that $\hat Z_M$ is irreducible over $K(\bv)$, and give three self-contained proofs that the Galois group of $\hat Z_M$ over $K(\bv)$ is the symmetric group of degree $… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Note that we have achieved every transitive permutation group of degree at most 4, but for degree 5 we are missing the cyclic group. The unique example of the dihedral group D 5 occurs for R (1,4,4,9,9,9,25). For degree 6, we have seen only five of the 16 transitive groups.…”
Section: Galois Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that we have achieved every transitive permutation group of degree at most 4, but for degree 5 we are missing the cyclic group. The unique example of the dihedral group D 5 occurs for R (1,4,4,9,9,9,25). For degree 6, we have seen only five of the 16 transitive groups.…”
Section: Galois Groupsmentioning
confidence: 99%
“…It was shown by de Mier et al [13] that, for a connected matroid (in particular, for a 2-connected graph), the two-variable Tutte polynomial is irreducible. Furthermore, Bohn et al [4] showed that, under the same hypotheses, the multivariate Tutte polynomial (regarded as a polynomial in the global variable over the field of fractions of all the local variables) has Galois group the symmetric group. Thus, one would expect that "almost all" specialisations of this polynomial would have symmetric Galois group.…”
Section: Further Speculationmentioning
confidence: 99%
“…In most (over 90%) cases the Galois groups are symmetric Galois groups. Recently, it was shown that the Galois group of the multivariate Tutte-Whitney polynomial is always a direct product of symmetric groups [8]. The chromatic polynomial is an evaluation of this polynomial.…”
Section: Introductionmentioning
confidence: 99%